Spending Behaviour of a Case of Asian University Students - Shahryar, Sorooshian; Tan, Seng Teck* (Canadian Center of Science and Education, 2014)
Recently, interest in exploring professional financial issues mainly money management was shown to be highly increased due to the societal awareness of its benefits. The skill of money management is a major tool in exercising control over them to obtain quality life as working adults. Stratified random sampling was used to examine the spending patterns of student population at one of Malaysia universities. Due to the habit of student expenditures on campus which was shown to influence the way money is managed through their lives. Taking a look at literatures from researchers outside Malaysia, it can be seen that financial literacy among students is required to restrain future problems that may arise from lack of knowledge on individual financial management. This study emphasizes the need on financial literacy awareness among the students looking into their background, financial awareness, attitude and family. Data analysis show that majority of the students do not put to practice correct skill in money management.